2013
DOI: 10.1016/j.aller.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Specific oral tolerance induction in paediatric patients with persistent egg allergy

Abstract: Our SOTI protocol is a safe, effective treatment for food allergy and of reasonable duration, confirming that tolerance can be induced in children who have not achieved it spontaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
67
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 16 publications
8
67
3
Order By: Relevance
“…In a randomized clinical trial, comparing the efficacy of OIT and elimination diet in the treatment of children with egg allergy, among 40 patients in the OIT group, 1 was withdrawn from the trial because of EoE development [56] .…”
Section: Oit and Eosinophilic Esophagitismentioning
confidence: 99%
“…In a randomized clinical trial, comparing the efficacy of OIT and elimination diet in the treatment of children with egg allergy, among 40 patients in the OIT group, 1 was withdrawn from the trial because of EoE development [56] .…”
Section: Oit and Eosinophilic Esophagitismentioning
confidence: 99%
“…Other trials of egg, milk, or peanut OIT have reported lower rates of reactions during dosing (25-45 %), with generally mild reactions limited to oral or pharyngeal symptoms [8•, 9, 11, 13••, 15•]. However, a number of [22][23][24][25][26]. Lucendo and colleagues performed a systematic review with meta-analysis and estimated the prevalence at 2.7 % [27].…”
Section: Oral Immunotherapymentioning
confidence: 99%
“…5 After 10 weeks, the patient experienced vomiting and facial erythema after the ingestion of 1 g of powdered pasteurized egg (one tenth of egg). The active substance was replaced with cooked egg (omelet) to continue with the protocol.…”
mentioning
confidence: 99%
“…5 Children who obtained desensitization to cooked eggs did not necessarily reach complete desensitization to raw egg white. 6 However, according to our experience, 54% of children who completed oral desensitization treatment with cooked egg had good tolerance to raw egg white.…”
mentioning
confidence: 99%
See 1 more Smart Citation